Refixation Saccades with Normal Gain Values: A Diagnostic Problem in the Video Head Impulse Test: A Case Report - Korsager, Leise Elisabeth Hviid; Faber, Christian Emil; Schmidt, Jesper Hvass; Wanscher, Jens Højberg (Frontiers in Neurology, 2017)
Refixation saccades with normal gain value occur more frequently with increasing age. The phenomenon has also been observed in different vestibular disorders. In this case we present a young male with normal gain value and refixation saccades tested with the video head impulse test (vHIT) the day after his cochlear implantation. One month after surgery refixation saccades were no longer present. This suggests that refixation saccades can occur from a temporary pathology such as surgery. Refixation saccades with normal gain values might reflect a partial deficit in the vestibulo-ocular reflex (VOR). This partial deficit is however in conflict with the current way of interpreting a vHIT result classifying the vestibular function as either normal or pathologic based only on the gain value. Refixation saccades, which are evident signs of vestibulopathy, are not considered in the evaluation. A new way of interpreting the vHIT based on the saccades must be considered.